Time-Stratified Case Crossover Study of the Association of Outdoor Ambient Air Pollution With the Risk of Acute Myocardial Infarction in the Context of Seasonal Exposure to the Southeast Asian Haze Problem - Ho, A.F.W. (American Heart Association Inc., 2021)
10.1161/JAHA.118.011272